EFL students’ challenges in TOEIC® updated test: listening section - Zewitra, Zewitra; Purnamasari, Yessy (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The TOEIC® Listening and Reading Test has been updated since 2018 and has been utilized for various purposes. This present study attempts to investigate the challenges faced by EFL students in achieving certain desired scores on the TOEIC® Updated Test, particularly in the listening section. This study employed qualitative methodology and CBT (computer-based test) of TOEIC® updated test was used as the instrument. Data was taken from the test results of 52 participants who joined POLBAN’s (Politeknik Negeri Bandung) TOEIC® Preparation and Prediction for IISMA 2024 conducted in January 2024. The results reveal that in solving the listening section in the TOEIC® Updated Test, test takers encounter difficulties in 12 different targeted skills. Some targeted skills are considered more challenging than others, i.e., understanding information questions and tag questions in the listening part II and making inferences as well as understanding graphics in the listening part IV. Surprisingly, understanding graphics is one of the new types of questions in the TOEIC® Updated Test. The fruitful implications of this study, both theoretically and practically, will be further explained in this article.